Beyond the Classroom Walls: A Scoping Review of Immersive Strategies for Teaching Arabic Culture - Cherkaoui, Driss (Universitas Andalas, 2025)
This study is situated within the context of contemporary foreign language education wherein cultural understanding is considered integral to linguistic proficiency, particularly in the diverse field of Arabic pedagogy. Still, despite the prevalent use of out-of-class activities, few studies have explored the full range of these strategies systematically. The current study fills a gap by providing a comprehensive overview of the evidence supporting these methods. The main objective of this study is to identify, categorize, and document the extracurricular strategies used for teaching Arabic culture to non-native speakers. The research design involved a five-stage scoping review following the Arksey and O'Malley framework. Data were collected through a systematic search of electronic databases (including Google Scholar, Scopus, and Dar Al-Mandumah) using keywords in both English and Arabic, resulting in a final dataset of 35 relevant scholarly sources out of 1,250 previous studies. The data were analysed using thematic analysis to chart, collate, and identify recurring strategies and themes across the literature. The analysis uncovered five dominant extracurricular strategies: (1) homestays, (2) language partner programs, (3) structured field trips, (4) community-based service-learning, and (5) cultural clubs and media workshops. Key results pinpoint a profound scarcity of rigorous empirical research, an absence of comparative studies, and a strong geographical bias in the literature toward Egypt and Morocco. This research provides evidence of a growing consensus on what strategies are used at the expense of their relative effectiveness. With this in mind, the study urges future research to conduct more empirical, comparative, and geographically diverse studies, deploying reliable and validated tools to measure cultural competence and cultural sensitivity.